PENGARUH UMUR PERUSAHAAN, EARNING PER SHARE, DEBT TO EQUITY RATIO, RETURN ON EQUITY, REPUTASI UNDERWRITER, DAN PERSENTASE PENAWARAN SAHAM TERHADAP UNDERPRICING PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING (IPO) TAHUN 2009-2015 - Susi Susilowati, 13.05.52.0017; Susilowati, Yeye (Students' Journal of Accounting and Banking, 2017)
This research was conducted to examine the effect of firm’s age, earning per share, debt to equity ratio, return on equity, underwriter reputation and the precentage of offers in that companies do an initial public offering (IPO) in the 2009 to 2015. Sampling method used in this study was purposive sampling method, which was based on certain criteria. Sampel that match with the criteria of this research were 115 companies do an initial public offering (IPO) in the period 2009-2015. The analysis used was multiple regressions, to see wheter the independent variables influence the dependent variable jointly or individually, preceded by normality test and assumption of classical test for test of multicolliniearity test, autocorrelation test, and heteroscedasticity test. The result of the data analysis or the regression indicate that the firm’s age, debt to equity ratio, return on equity and underwriter reputation negative effect on the level of underpricing, while earning per share and the precentage of offers positive effect on the level of underpricing.Keywords: Underpricing, Firm’s Age, Earning Per Share, Debt to Equity Ratio, Return On Equity, Underwriter Reputation, The Precentage of Offers, and initial Public Offering